Investigating the Willingness of Sharing Real-Time Daily Activities among Friends. Issue 7 (20th April 2020) - Chen, Ling; Dong, Miaomiao; Wang, Liwen; Chen, Gencai
ABSTRACT: With the development of technology, mobile and wearable devices can obtain many different kinds of real-time activities from users. In social domains, the sharing of real-time activities is proved to help users to understand the current state of others and promote social relationships. However, most studies focused on real-time simple activities sharing, and the willingness of sharing real-time daily activities has not been fully studied. In this paper, we conduct an in-situ study to explore the willingness of sharing real-time daily activities among friends and study the factors that could influence sharing willingness. We find that daily activity types, friend types, location types, time periods, and participants' privacy attitude classifications could influence sharing willingness. Our findings provide a basis for real-time communication systems to support the sharing of different types of daily activities. Furthermore, we present some design implications to better support real-time daily activities sharing.